2017
DOI: 10.1002/oby.21968
|View full text |Cite
|
Sign up to set email alerts
|

The Primary Results of the Treating Adult Smokers at Risk for Weight Gain with Interactive Technology (TARGIT) Study

Abstract: ObjectiveTo evaluate whether a behavioral weight management program combined with a smoking cessation program delivered via interactive technology could prevent post-cessation weight gain.Methods330 young adult smokers age 18 to 35 were randomized to a smoking cessation program alone (Comparison group) that included behavioral counseling and nicotine replacement or to a behavioral weight management program adapted from the Look AHEAD trial plus the same smoking cessation program (Intervention group).ResultsTAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Of the 51 included studies, a total of 43 measured change in weight, with 41 of these having an objective measure of weight and two using a self‐report measure for weight . This includes 19 studies from the meta‐analysis and a further 24 studies that reported weight as an outcome with results in a format that was not compatible for inclusion in the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 51 included studies, a total of 43 measured change in weight, with 41 of these having an objective measure of weight and two using a self‐report measure for weight . This includes 19 studies from the meta‐analysis and a further 24 studies that reported weight as an outcome with results in a format that was not compatible for inclusion in the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Of these 43 studies, 14 reported statistically significant between‐group reductions in weight (as shown in Table S2). Of the 43 studies, 15 were weight loss interventions and 28 were weight‐gain prevention interventions . Specifically, for the weight loss studies, four of the 15 (27%) demonstrated significant reductions in weight when compared with control .…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 includes a brief description of each of the treatment arms organized by intervention target: weight loss (WL); weight gain prevention (WGP); or weight management among special populations (SP). Table 1 also shows the variability of intervention dose and delivery methods as planned and the variability of average weight change after 12 months (2,4,6,7,2022). For decomposition purposes, five arms were considered true controls hereafter called “controls”; the remaining 12 arms including active controls and intervention are called “interventions”.…”
Section: Resultsmentioning
confidence: 99%
“…Three of the studies focused on weight loss (IDEA, (2), CITY, (3), SMART, (4)). Two studies focused on weight gain prevention (SNAP, (5) CHOICES, (6)), and two studies focused on other outcomes in special populations including preventing weight gain during smoking cessation attempts (TARGIT, (7)), and gestational weight gain and post-partum weight loss (eMoms, (8)). All EARLY interventions were delivered using technology, including the internet, cell phones, apps, and exercise tracking devices.…”
Section: Introductionmentioning
confidence: 99%
“…The TARGIT study, a recent efficacy trial testing combined tobacco and weight management treatments also found no significant intervention effects or differences on tobacco abstinence or weight gain. Controls gained an average of 1.45 kg; the intervention group gained an average of 0.32 kg [ 33 ]. The weight gain reported in the Spring et al.…”
Section: Discussionmentioning
confidence: 99%